(untitled) (International Journal of Medical and Surgical Sciences, 2016)
The radicular cyst is the most common injury in the jawbone, and the lateral incisor is the most affected tooth. The surgical technique allows a wide range of excision procedures to solve the eradication of injury, from the preservation of post-surgical blood clot to novel regenerative techniques. This case shows the result of the use of lyophilized human bone and resorbable membrane, after resection of radicular cyst as successful procedure.